Acute effects of exercise on cardiac autonomic function and arterial stiffness in patients with stable coronary artery disease. (1st December 2021) - Angarten, Vitor; Melo, Xavier; Pinto, Rita; Santos, Vanessa; Marôco, João Luís; Fernhall, Bo; Santa-Clara, Helena
Abstract: Objectives. To examine the acute effect of a maximal aerobic exercise effort on aortic, peripheral arterial stiffness and cardiovagal modulation of trained and untrained patients with coronary artery disease (CAD). Design . Cross-sectional study. Methods . Eighteen untrained patients with CAD, 18 trained patients with CAD, and 18 apparently healthy trained subjects were sampled and matched for age and body mass index. Aortic and peripheral stiffness were measured by applanation tonometry estimates of carotid-femoral (cfPWV), carotid-radial (crPWV), and carotid-dorsalis pedis pulse wave velocity (cdPWV), respectively. Cardiovagal modulation was assessed by heart-rate variability (HRV) indices including the standard deviation of normal-to-normal RR intervals (SDNN), root-mean-square of successive differences (RMSSD), and the high-frequency power band (HF). cfPWV, crPWV, cdPWV, and HRV indices were measured at rest, 10 and 30 min following a maximal cardiopulmonary exercise test on a cycle ergometer. Results . No differences were observed between groups at rest nor over time in indices of HRV, cfPWV and cdPWV. Still, main effects of time were observed in cfPWV ( p  < .001; ɳ 2 = 0.313) and cdPWV ( p  = .003, ɳ 2 = 0.111), RMSSD ( p  < .001, ɳ 2 = 0.352), HF ( p  < .001, ɳ 2 = 0.265) and LF/HF ( p  = .001, ɳ 2 = 0.239), as cdPWV, RMSSD, and HF were reduced 10 min following exercise, whereas cfPWV and LF/HF were increased. Changes in cPP were associated with changes in HRV from rest to min 10 (HF, r  = 0.302), and to min 30 (HF, r  = 0.377; SDNN, r  = 0.357; RMSSD, r  = 0.429). Conclusion . Training level and CAD do not seem to influence arterial stiffness and cardiac autonomic responses to maximal exercise.